Interaction of modulated REB with plasma, formed at its transit through high-density neutral gases - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Sotnikov, G.V.; Uskov, V.V. (Вопросы атомной науки и техники, 2003)
The theoretical and experimental results of investigations of the relativistic electron beam interactions with plasma, created during its penetration into neutral gas of large pressure, are presented. It is shown that by using of deeply modulated beam it is possible to avoid the depressive influence of dissipation and longitudinal nonuniform plasma density on the beam-plasma interaction efficiency. Представлені теоретичні та експериментальні результати досліджень взаємодії релятивістського електронного пучка з плазмою. Показано, що при використанні глибоко промодульованих пучків можливо уникнути пригнічення пучково-плазмової нестійкості дисипацією і поздовжньою неоднорідністю плазми. Представлены теоретические и экспериментальные результаты исследований взаимодействия релятивистского электронного пучка с плазмой. Показано, что при использовании глубоко промодулированных пучков возможно избежать подавления пучково-плазменной неустойчивости диссипацией и продольной неоднородностью плазмы.